Livestock Activity Data Guidance (L-ADG): Methods and guidance on compilation of activity data for Tier 2 livestock GHG inventories - Wilkes, Andreas; Pica-Ciamarra, Ugo; Opio, Carolyn (Food and Agriculture Organization of the United Nations, 2020)
The Livestock Activity Data Guidance (L-ADG) provides practical methods for countries to estimate the activity data used to compile livestock GHG inventories using the IPCC Tier 2 approach. The purpose is to support countries to improve the accuracy of the livestock emission estimates in national GHG inventories, and thus enable countries to measure and report progress towards their NDCs.